Academic training during the COVID-19 pandemic: Analysis and impact on students' mental health (Research, Society and Development, 2022)
Introduction: Emergence in China with the first case on December 1, 2019, an infection causing severe pneumonia, with initially unknown causes, later called COVID-19. Faced with these situations, some teaching and learning strategies were necessary for this adaptation, so that it was possible to continue teaching and not cause delay in the formation of academics. From this conception, distance learning caused some dissatisfaction and inconvenience in students. Objective: To analyze how students felt during the pandemic with all the changes made to maintain the flow of teaching through online platforms. Methodology: The planning of the present descriptive, qualitative field study, associated with a narrative bibliographic review of the literature. Results and Discussion: Traditionally, universities disseminate knowledge in the face-to-face format, believing that it allows practices with the student to better fix the contents, direct assistance with the teacher, social interactions with other students and other extracurricular activities. With the period of social isolation, faculties had to review their traditional teaching model, thus adopting an emergency teaching character that was characterized with remote teaching, aiming not to delay the academic development of students, which contributed to the emergence of mental diseases in academics. Final Considerations: The pandemic touched upon pre-existing mental disorders in the Brazilian population, with an emphasis on university students, as a result of the need for their rapid adaptation in remote classes along with several issues included in an emergency.